A Catalyst for Change? A Systems Analysis of the New Admissibility Test Developed in R v. Hart [2014] - Bateman, Jordan (Université d'Ottawa / University of Ottawa, 2017)
Past research has highlighted various problematic issues related to the use of the RCMP undercover operation entitled the “Mr. Big” sting. In a landmark decision, R v. Hart [2014], the Supreme Court of Canada recognized many problems with it and implemented a new admissibility test that would render confessions obtained by the undercover operation presumptively inadmissible. This research project explores the impact that this new evidentiary rule has had on cases involving “Mr. Big” confession evidence since the Hart decision (2014 to 2016). A content analysis was conducted on 16 cases that applied the new admissibility test. The case analysis revealed several important findings from cases that have applied the new admissibility test following Hart. In order to situate these findings, General Systems Theory was used to illustrate the impact that the court’s interpretation of the new evidentiary rule could have on the different components of the criminal justice system. It will be important for future research to further examine the impact of the new admissibility test in order to enhance our understanding of the influence it has had on cases involving “Mr. Big” sting confession evidence.
Keywords: Mr. Big Sting; Undercover Operations; General Systems Theory; Content Analysis; R v. Hart; Admissibility Test; Unreliable Confessions